Translation and Validation of the Typology of the Aged with Illustrations Measurement in the Thai Version - Peawnalaw, Supannee; Chatrung, Chutikarn; Mahaprom, Tiwa (NU Journal of Nursing and Health Sciences, 2022)
This research aimed to translate and examine the validity and reliability of the Typology of the Aged with Illustrations in the Thai version. The English version was translated into Thai using the five steps of a back-translation method (Brislin, 1970; 1986). The participants were 322 older adults. The research instrument was Barthel ADL Index and the Typology of the Aged with Illustrations. The demographic data were analyzed by using descriptive statistics. The Item and scale level content validity index were computed for content validity and criterion-related validity was analyzed by using Pearson product moment correlation.The results revealed that the Thai version of the Typology of the Aged with Illustrations had content and semantic validity as compared to the original version. The Item-level content validity index were 89 .89 1.0 .89 and Scale-level content validity index was .92. The criterion-related validity showed a high score for group identification and positively correlated with Barthel ADL index at a statistically significant level of .05. Moreover, Cronbach’s Alpha was .87. The research findings indicated that the Typology of the Aged with Illustrations in the Thai version had high content validity and reliability. It can be used for categorizing the group of older adults to provide appropriate nursing care.